China's Fight Against COVID-19: What We Have Done and What We Should Do Next? - Cheng, Sixiang; Zhao, Yuxin; Kaminga, Atipatsa Chiwanda; Zhang, Xinping; Xu, Huilan (Frontiers in Public Health, 2022)
Background Chinese government conducted unprecedented massive public health prevention interventions at the national level, which have effectively contained the spread of Coronavirus Disease 2019 (COVID-19) infections. Specifically, the outbreak in Wuhan has been effectively controlled. Meanwhile, the Chinese efforts to contain the virus have been widely recognized. Even the World Health Organization has praised the efforts of the Chinese government and advised other countries to learn from China's experience in the fight against COVID-19. However, the measures that have been conducted by China to effectively prevent the spread of COVID 19 in the country have not been rigorously analyzed. Therefore, this study aimed to explore the characteristics of China's control and prevention strategies, and identify the elements that changed the epidemiological curve of rapidly rising new confirmed cases of COVID-19. Methods Public health intervention measures and their effects on the spread of COVID-19 in terms of daily newly confirmed and cumulative cases were collected between January 20, 2020, and March 5. Notices of the Joint Prevention and Control Mechanism for COVID-19 of the State Council on Implementing Measures in Hubei were collected. Information obtained by relevant important documents and announcements was collected from the official website of the Chinese government. Additionally, from other media platforms, news, articles, and reviews were used to explain the intervention measure. Thus, using these data, we performed a retrospective description of the intervention strategies at three stages. Results The Chinese government adopted non-pharmacological interventions measures (NPIs) timely and efficiently. On February 20, the declining epidemic trend in China indicated that the three strictest disease prevention and control strategies issued by the Hubei Government had contributed to a smooth decline in the spread of the epidemic. Conclusions The NPIs taken by China play a decisive role to control the spread of novel coronavirus outbreaks. Further research and action are needed to ensure a sufficiently sensitive surveillance system and strong response mechanism, including the establishment of a highly accessible laboratory network, maintenance of awareness of both primary healthcare providers and the public, and regular training and exercise of local Centers for Disease Control and Prevention and general practitioners in the community-level.